Existence and uniqueness of the solutions of some classes of integral equations C*-algebra-valued b-metric spaces - Jakupović, Esad; Masiha, Hashem P.; Mitrović, Zoran; Razavi, Seyede S.; Saadati, Reza (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: The aim of the paper is to establish some coupled fixedpoint results in C*-algebra-valued b-metric spaces. Moreover, the obtained resultsare used to define the sufficient conditions for the existence of the solutionsof some classes of integral equations.Methods: The method of coupled fixed points gives the sufficient conditions forthe existence of the solution of some classes of integral equations.Results: New results were obtained on coupled fixed points in C * -algebra-valuedb-metric space.Conclusion: The obtained results represent a contribution in the fixed point theoryand open new possibilities of application in the theory of differential and integralequations.
Keywords: Coupled fixed point; C*-algebra; integral equation